2021
DOI: 10.1088/1361-6528/abe260
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemical and microstructural inhomogeneities on interface magnetism

Abstract: The study of interfacing effects arising when different magnetic phases are in close contact has led to the discovery of novel physical properties and the development of innovative technological applications of nanostructured magnetic materials. Chemical and microstructural inhomogeneities at the interfacial region, driven by interdiffusion processes, chemical reactions and interface roughness may significantly affect the final properties of a material and, if suitably controlled, may represent an additional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Due to the difficulty in directly characterizing the AFM spin structures, there are still controversies in understanding the mechanism of noncollinear IEC across AFMI layer [18,19,21]. Additionally, while interface mixing is commonly observed in FM/AFMI heterostructures [22][23][24][25][26][27], which can modify the nearest-neighbor exchange across the interface [28,29], its impacts on the IEC are seldom reported. Although the origin and modifications of the noncollinear IEC is still under intense research, its applications in sensors and spintronic devices deserve attention.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difficulty in directly characterizing the AFM spin structures, there are still controversies in understanding the mechanism of noncollinear IEC across AFMI layer [18,19,21]. Additionally, while interface mixing is commonly observed in FM/AFMI heterostructures [22][23][24][25][26][27], which can modify the nearest-neighbor exchange across the interface [28,29], its impacts on the IEC are seldom reported. Although the origin and modifications of the noncollinear IEC is still under intense research, its applications in sensors and spintronic devices deserve attention.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that in many of these heterostructures, interfacial mixing and dead layers exist at the interfaces of magnetic and non-magnetic layers. Such interfacial compositional heterogeneities have led to varying magnetic properties, such as thickness-dependent anisotropy and magnetization [15][16][17][18][19][20][21] . These present challenges in fabricating and developing devices with magnetic thin films, such as magnetic tunnel junctions 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The surface [ 25 , 26 ] contribution can be controlled through the interaction with another phase in contact with it, i.e., exploiting the interface effect, which can be of different type depending on the nanoparticle system and the nature of the two phases in contact [ 27 ]. As an example, in bimagnetic core/shell particles, combining ferromagnetic and antiferromagnetic phases, the exchange coupling at the interface between the core and the surface shell can give rise to the exchange bias phenomenon [ 28 , 29 ], which is often accompanied by an increase of anisotropy, due to the so-called “exchange anisotropy”.…”
Section: Introductionmentioning
confidence: 99%